The continuity of social times in China - Wei Zhao; Jens Thoemmes (Temporalités)
Our article presents the result of a common two-year research project about social times in China. It uses French sociology theory and a case-study approach. A shoe and a steel factory including semi-structured interviews with workers (n: 25) are the basis of our analysis. Our results show the importance of the discontinuity of social times in Chinese manufacturing industries. They indicate specific configurations of rules in those industries associating subsistence time, continuity time and a projected future.